Sustainable Development Management Factors in The Regional Economy of Ukraine - Borodina, Oksana; Burdonos, Lyudmila; Stetsenko, Volodymyr; Kovtun, Oleksandr (Dr. Viktor Koval, 2022)
Introduction. The functioning of the Ukrainian economy with a large number of restrictions necessitates its restoration on the basis of high-quality strategizing, taking into account foreign experience. The formation of financial support tools for the development of a regional development strategy raised the question of the need to change financial strategies to ensure the conditions for sustainable development, which determined the relevance of the study. Aim and tasks. The aim of this study is a theoretical and methodological review of modern financing of regional projects in Ukraine at the subregional level and the provision of proposals for their conceptual improvement in order to ensure sustainable development of the economy based on the European experience of regional strategizing. Results. The research contains a thorough modern analysis of individual factors of sustainable development of the regions of Ukraine in the medium-term perspective, namely: use of the opportunities of the administrative-territorial system; effective financing of regional development; concepts and models of "green" development of the regions of Ukraine. The need to organize a qualitatively new financing of regional development with the aim of achieving stable economic growth in post-war Ukraine is substantiated, and ways and forms of state assistance for this process are proposed. Based on the indicators of tax revenues in Ukraine in 2015–2021, a conceptual model of a system of institutions at the district (subregional) level is proposed that contributes to regional development, taking into account smart specialization and environmentalization. For its effective functioning, a mechanism for financing such a system is proposed based on the fiscal scheme of deductions from corporate income tax in the estimated amount for each territorial level. Conclusions. Synchronization of the administrative-territorial division with European countries made it possible to implement the EU experience in financial support of the sub-regional level of management and to offer a new vision of this process in Ukraine. Forecast calculations of the percentage of deductions from the tax revenues of enterprises' income tax to the relevant development funds were carried out using the apparatus of economic and mathematical modeling. The prospects for sustainable development and models for achieving this goal are analyzed, within which the vision, regional, and sectoral goals of such models are systematized.